(3GdJWhQGJ GdGbJUGOjI GdMOjKI hCKQgG Ydi eQcR GdeJYGbOjf aj GdYbO GdEOGQj (B: s (3OQGSI ebGQfI (B/ s - (3MGRe Hjhej GdeUQjs; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2008)
(3gPg GdQSGdI JOhQ hLhOG h YOeG aj adc GdJWhQGJ GdGbJUGOjI GdMOjKI hCKQgG Ydi eQcR GdeJYGbOjf aj GdYbO GdEOGQi h Pdc ef NdGd efGbTI GdJWhQGJ GdGbJUGOjI GdMOjKI h GdfXQjI GdJbdjOjI ddYbO GdEOGQi Yf WQjb HjGf GdJWhQGJ GdGbJUGOjI GdMOjKI h GdGJLGg fMh JRGjO CgejI GdYbhO GdEOGQjI OhdjG h CSS GdfXQjI GdJbdjOjI ddYbO GdEOGQi(B. (3h ChVMfG CKQ gPg GdJWhQGJ Ydi eQcR GdJYGbOjf aj eQMdI Jchjf GdYbO eJfGhdjf eYGdLI GNJdGd GdJhGRf Hjf GdeJYGbOjf aj gPg GdeQMdI h eXGgQ GNJdGd GdJhGRf Hjf GdeJYGbOjf aj eQMdI ESfGO GdYbOs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2008s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdEOGQjs; (3GdJWhQGJ GdGbJUGOjI GdMOjKIs; (3GdYbO GdEOGQis; (3GdbGfhf GdOhdjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdEOGQjs